Why do Urban Young Adults Share Online Video Advertisement in Malaysia? - Goh, See Kwong; Tan, Inn-Shen; Yeo, Cheow Sern Vincent (International Review of Management and Marketing, 2016)
The purpose of this study is to investigate the factors that will influence young adults in the urban areas to share online video advertisement. In this study, the authors have shortlisted four important variables, namely extrinsic motivation, information sharing, pleasure seeking and social influence in affecting one's behavior towards sharing online video advertisement. A total of 168 participated in this study. A multiple linear regression analysis was adopted to examine the relationship between the variables. Results indicated that all hypotheses were significant. This research provides an in depth insight about the factors contributing to sharing of online video advertisements. Marketers could develop video ads that encourage consumers to share via their social network sites. Video ads shared by users are perceived to be less skeptical as compared to those shared by companies and it could achieve wider audience. Keywords: sharing online video advertisements, extrinsic motivations, pleasure, information sharing, social influence JEL Classifications: M310, M730